Demographics of cystic echinococcosis patients treated surgically in Lahore, Pakistan: A single centre study from 2007-2018 - Rasib, Q.; Khan, A.; Ahmed, H.; Nizamuddin, S.; Asif, F.; Afzal, M. S.; Budke, C. M. (Sciendo, 2021)
Cystic echinococcosis (CE) is a zoonotic disease caused by the larval stage of Echinococcus granulosus tapeworms. These parasites have a worldwide geographic distribution and pose a serious threat to livestock industry as well as human health in the endemic areas. CE is widely distributed in Pakistan. However, very few reports are available related to the regional transmission of E. granulosus. A retrospective analysis was conducted of surgically confirmed CE patients who were treated at Shoukat Khanum Memorial Cancer Hospital and Research Centre in Lahore, Punjab Province, Pakistan from 2007 - 2018. In total, 536 CE patients were evaluated during the study period. Cases originated from the provinces of Khyber Pakhtunkhwa (n=336), Punjab (n=147), Baluchistan (n=18), Sindh (n=3), Islamabad (n=2), Gilgit Baltistan (n=1), and Azad Jammu and Kashmir (n=1). An additional 28 cases were from Afghanistan. The highest number of CE cases was reported in 2013 (n=90). Females made up a larger proportion of cases (n=310; 57.8 %) than males (n=226; 42.2 %). Most patients were members of the Pashtun (n=197; 36.7 %), Hindku (n=142; 26.5 %), and Punjabi (n=118; 22.0 %) ethnic groups. The largest number of cysts was obtained from the liver (137/536; 25.6 %). This study showed that CE is likely present throughout Pakistan. In order to control the disease, a comprehensive control program and regional surveillance are needed.
Keywords: Cystic echinococcosis; epidemiology; human; Pakistan